BEYOND MECHANICAL SKILLS IN THE ENGLISH LANGUAGE CLASSROOM: WORKING WITH FAKE NEWS FROM THE DIGITAL LITERACIES PERSPECTIVE - Silva, Nayara Stefanie Mandarino (Revista de Estudos Acadêmicos de Letras, 2020)
The advances in technology and the access to internet contribute to the spread of fake news, a phenomenon that is not new, but that is happening in a new environment – the cyberspace. Considering this reality, there have been debates related to how people (should) deal with information in the so-called post-truth era. Language is crucial in both the production and interpretation of fake news; English stands out in this process due to its number of users all over the world. One of the possibilities to deal with this phenomenon in the English language class is the digital literacies theory discussed in this paper which aims at analyzing an experience with fake news in the English classroom, focusing on possibilities in the development of digital literacies skills to deal with this kind of news. Regarding the methodology, this paper is a qualitative – analytical-interpretative – research. The analysis was based on Freeman’s (1998) four steps: naming, grouping, finding relationship, and displaying. Finally, I conclude that working with the digital literacies theory in the English classroom can help students deal with fake news, considering that it requires not only mechanical skills, but also reflection on how and why we interpret texts the way we do.